ENHANCING LITERACY AND ATTITUDES TOWARD CASH WAQF THROUGH DIGITAL STORYTELLING - Purnama Putra; Reza Anggriyashati Adara (Referensi Islamika: Jurnal Studi Islam, 2026)
The study intends to investigate the effectiveness of digital storytelling in enhancing literacy and forming attitudes toward cash waqf among a group of college students majoring in Islamic banking study. This study applied a quasi-experimental design without a control group due to the limited number of participants. Twenty college students were involved in this study. In addition to a seven-week treatment, a set of questionnaires and semi-structured interviews were administered to the participants. The results demonstrate that the participants’ literacy levels and attitudes toward cash waqf showed an improvement after being taught using digital storytelling. Additionally, the participants showed enhanced understanding of the practical applications and benefits of cash waqf for ummah.  The present study is restricted by the relatively small number of participants and the absence of control group, limiting generalizability and causal inference. Hence, future studies should include larger samples and comparative designs to increase the validity of the findings. This study provides better insights toward the integration of digital storytelling into cash waqf education, enabling an innovative and engaging approach to encourage financial literacy and social awareness in Islamic finance contexts.